ARQUEOLOGIA DA PROTOFICÇÃO CIENTÍFICA E A CONTRIBUIÇÃO DA LITERATURA MARANHENSE - SOUSA, Thalita Ruth (2021)
The archeology of Science Fiction (SF) is rooted in traditional and mythological narratives, shaping a body of literatures named mega-text, which includes scientific speculations as well as aesthetic formations of the Fantasy, Fantastic, Horror and Gothic. This hybridization, the presence of science and the incorporation of icons currently known as components of SF are distinctive aspects of the Protoscience Fiction. This literary manifestation is identified in the national context since the mid-nineteenth century. Its figures and themes, referred as novums, allow parallels with productions of Luciano de Samosata, Johannes Kepler, Ernest Hoffman, Jules Verne, H. G. Wells and Edgar Allan Poe. The socio-ideological transformations from the Tropical Belle Époque altered the Brazilian science epistemology, especially in the 1900-30 decades.This provoked an artistic reaction reverberated in literature, mainly in the figure of the scientist, as exemplify the tales which are object of this thesis: “A Sombra” (1927) and “Morfina” (1932), respectively written by the Maranhense imortals Coelho Neto (1864-1834) and Humberto de Campos (1886-1934). Thus, this bibliographical research aims to analyze the national Protoscience Fiction, especially the Maranhense contribution, showing how it portrays the reactions to the scientific development of the country. Given that, this study adopts the theoretical and critical basis of Adrienne Mayor (2018), Damien Broderick (1994), Darko Suvin (1979) and Naiara Araújo (2020) related to SF; concerning Brazilian aspects, Alexander Meireles (2008), Elizabeth Ginway and Roberto Causo (2010); and about historical and scientific aspects, Mary Del Priore (2014), Carla Mazzio (2009) and Shozo Motoyama (2004). As a result, it is highlighted that escapist elements as the supernatural, madness and monstrosity burst into the reality of the narrative in consequence of science making failures, representing the fears of a population towards the exploration of the unknown. However, as the literature reflects changings originated from the tecno-scientific advance, this hybridization loses its expressiveness and the stories increasingly resemble the characterization of the SF genre.